IMPACT OF PHOTOPERIOD ON CIRCADIAN PROTEIN AND PROTEASE RHYTHMS IN THE DIGESTIVE SYSTEM OF SILKWORM, BOMBYX MORI - E. BHUVANESWARI; S. SIVAPRASAD (The Bioscan, 2012)
Photoperiod-induced clock-shifting in circadian protein and protease rhythms were studied in the larval digestive system of Bombyx mori under 12h light-dark cycle (LD), continuous light (LL) and continuous dark (DD) conditions. The hourly changes, reflected as peaks and troughs in the phase response curves of protein and protease rhythms, were interpreted as protein synthetic cycles in gut wall and protein releasing cycles in gut content. In the gut wall, the protein rhythm showed 6 synthetic cycles of 4h duration each under LD and 7 cycles of 3.4h duration each under LL and DD. As a result, the 24h-free running period of LD rhythm is advanced to 20.4h under LL and DD. The gut wall protease rhythm maintained 6 synthetic cycles of 4h duration each under LD and DD and 7 cycles of 3.4h duration each under LL. Consequently, the 24h protease rhythm of LD and DD is advanced to 20.4h under LL. The gut content protein rhythm showed 6 releasing cycles of 4h duration each under LD, 7 cycles of 3.4h duration each under LL and 5 cycles of 4.8h duration each under DD, resulting in rescheduling of the 24h LD rhythm to 20.4h under LL and 28.8h under DD. However, the gut content protease rhythm maintained 7 releasing cycles, each with duration of 3.4h uniformly under LD, LL and DD. The analysis of mean peak values of proteins and protease levels reveal that dark cues are necessary for their synthesis and both dark and light cues are essential for their release.